Analisis Manajemen Pengelolaan Pesantren: Studi Kasus Manajemen Pesantren Al Khairot Malang - Hittotun Nahdiyah; Muhammad Husni (Jurnal Manajemen dan Ilmu Administrasi, 2026)
This study aims to analyze the management of Pondok Pesantren Al-Khoirot (PPA) Malang in implementing an educational system that integrates traditional values with modern innovations. The method used is qualitative field research with subject determination techniques through purposive sampling and time sampling. Data collection was conducted through interviews, observation, and documentation, which were then analyzed using data reduction and data display. The results indicate that PPA Malang applies an integrated education system combining character education, religious knowledge, general sciences, and soft skills. The pesantren's management merges traditional (salaf) methods, such as the study of classic texts (kitab kuning) using "makna gandul", with modern educational frameworks. Featured programs include optional Tahfidz Al-Quran and Modern Arabic, alongside mandatory formal education (Kejar Paket B/C) for school-aged students to ensure state-recognized academic credentials. The novelty and implications of this research highlight the pesantren's success in transforming its management to produce a generation of "scholar-clerics" (ilmuwan-ulama) who are adaptive to contemporary developments without abandoning their traditional religious identity. These findings are expected to contribute to the advancement of Islamic education management, particularly in the governance of contemporary Islamic boarding schools.